2017
DOI: 10.1016/j.ajog.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination and subsequent cervical cancer screening in a large integrated healthcare system

Abstract: Background Human papillomavirus vaccination may result in lowered intention to be screened for cervical cancer, potentially leading to gaps in screening coverage and avoidable cervical cancer diagnoses. Objective To examine the association between human papillomavirus vaccination and subsequent cervical cancer screening initiation and adherence to recommended screening intervals to detect gaps in screening coverage and inform future prevention efforts. Study Design A retrospective cohort study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 21 publications
7
30
0
Order By: Relevance
“…Our preliminary analysis showed that on the contrary, vaccinated women of all ages, as well as those aged 21–29, were more likely to be screened than unvaccinated women. These findings are consistent with previous research (Chao et al, 2017). Associations between vaccine receipt and cervical cancer screening were not significant in the multivariate adjusted analysis.…”
Section: Discussionsupporting
confidence: 94%
“…Our preliminary analysis showed that on the contrary, vaccinated women of all ages, as well as those aged 21–29, were more likely to be screened than unvaccinated women. These findings are consistent with previous research (Chao et al, 2017). Associations between vaccine receipt and cervical cancer screening were not significant in the multivariate adjusted analysis.…”
Section: Discussionsupporting
confidence: 94%
“…Large population‐based studies in Sweden and the US analyzing the association between HPV vaccination and subsequent cervical cancer screening initiation and compliance with recommended screening intervals have shown that HPV‐vaccinated women were more likely than their unvaccinated counterparts to initiate cervical cancer screening and to adhere to recommended screening intervals. These results highlight a potential emerging disparity in protection among vaccinated and unvaccinated women, with the latter being also less prone to seek and adhere to cancer screening …”
Section: Introductionmentioning
confidence: 91%
“…These results highlight a potential emerging disparity in protection among vaccinated and unvaccinated women, with the latter being also less prone to seek and adhere to cancer screening. 105,106 In terms of the perceived change in sexual activity or sexual intention following vaccination, the study by NHANES found no significant changes in the percentage of women reporting sexual activity or number of sexual partners between the pre-and post-vaccination era;…”
Section: Impact Of Vaccination On Cervical Screening Compliancementioning
confidence: 98%
See 2 more Smart Citations